Career paths among top executives in Danish interest groups - Binderkrantz, Anne Skorkjær (Politica, 2020)
In recent decades, interest groups in Denmark have become more professionalized. Many interest groups have large, professional secretariats, and even smaller groups have strengthened their administration. At the same time, researchers point to the emergence of a group of policy professionals occupying positions in management, politics and organizations – and frequently switching between the various sectors. The article maps the individuals who lead almost 200 Danish interest groups. It shows that many top executives are recruited from the public sector, while it is relatively rare for politicians to be recruited for top positions in interest groups. The organization elite is similar to other elites in terms of personal characteristics and educational backgrounds.